2012
DOI: 10.7763/ijiet.2012.v2.157
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media to Improve a Parent-School Relationship

Abstract: Family and school are two important institutions in children's lives, playing a crucial role in their overall development. Effective integration of these two institutions can benefit not only students but also schools, teachers and parents. This paper has purposed the use of social networking tools, such as Facebook, to improve a parent-school relationship. In this paper, a data analysis of digital behaviours and habits of parent involved in school Facebook is presented. School demonstrate responsiveness to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
5
Order By: Relevance
“…Sosyal ağ kullanımının etkili olmasının en önemli nedenlerinden birisi ise velilerin bu tür destekleme çalışmalarına zaman ve mekan sınırlaması olmadan katılabilmeleri olabilir. Alanyazındaki araştırmalar da aile katılımında Facebook, wikiler, Twitter, Whatsapp gibi sosyal ağ kullanılmasının onların bu sürece daha fazla katılmalarını, daha fazla iletişim kurmalarınıı ve okul -veli arasında bilgi paylaşımında bulunmasını sağladığını göstermektedir (Chairatchatakul, Jantaburom ve Kanarkard, 2012;Curtiss ve diğerleri, 2015;Olmstead, 2013).…”
Section: Sonuç Ve Tartışmaunclassified
“…Sosyal ağ kullanımının etkili olmasının en önemli nedenlerinden birisi ise velilerin bu tür destekleme çalışmalarına zaman ve mekan sınırlaması olmadan katılabilmeleri olabilir. Alanyazındaki araştırmalar da aile katılımında Facebook, wikiler, Twitter, Whatsapp gibi sosyal ağ kullanılmasının onların bu sürece daha fazla katılmalarını, daha fazla iletişim kurmalarınıı ve okul -veli arasında bilgi paylaşımında bulunmasını sağladığını göstermektedir (Chairatchatakul, Jantaburom ve Kanarkard, 2012;Curtiss ve diğerleri, 2015;Olmstead, 2013).…”
Section: Sonuç Ve Tartışmaunclassified
“…Twitter can be used to post reminders about events, share news of the day and share photographs and information from school-wide activities and class trips [7]. The related literature [16,33,55,18] has demonstrated that the use of social networks in parental involvement mostly entailed the use of school Facebook page or Twitter account and information posted on these platforms. Hernandez-Cruz and Russel's [33] study revealed that the school's Facebook page or twitter account increase the parent involvement, parents know what is going on in the school and teachers provide parents useful information about student learning.…”
Section: Recent Studies In Parental Involvement Via Social Mediamentioning
confidence: 99%
“…Hernandez-Cruz and Russel's [33] study revealed that the school's Facebook page or twitter account increase the parent involvement, parents know what is going on in the school and teachers provide parents useful information about student learning. Chairatchatakul, Jantaburom and Kanarkard [16] examined how school use Facebook to engage parents, foster relationship growth in parent-school and also to learn which school information the parents preferred in their study. The usage and application of the school Facebook Page in several features namely, presence of school information, questions, interesting links, events, places and photo and video albums.…”
Section: Recent Studies In Parental Involvement Via Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, it is not necessary to go to school in person for the family to participate in education. One of the best ways to ensure family participation in education is communication between the school and the parent (Chairatchatakul, Jantaburom, & Kanarkard, 2012). In other words, teacher-parent communication is part of parents' involvement in school activities (Hobjila, 2014).…”
Section: Introductionmentioning
confidence: 99%